Discrepancy in the Adequacy of Compensation for Land Acquisition between Public and Private Valuers - Arulraj, Priya Dharishini; Rozilah Kasim (Research in Management of Technology and Business, 2026)
This study examines discrepancies in determining adequate compensation for land acquisition between public and private valuers in Johor, grounded in Malaysia’s constitutional and statutory framework, which mandates fair compensation while acknowledging persistent valuation disputes. The objective is to identify the key factors contributing to these discrepancies and to determine their hierarchy of importance from the perspectives of public and private valuers within the state. A quantitative research design was employed, utilising a structured questionnaire distributed via Google Forms to public and private valuers in Johor. The data were analysed using SPSS, employing descriptive statistics, frequency analysis, and mean–standard deviation-based ranking on a five-point Likert scale. The findings reveal that nine main factors including Market Value, Physical Characteristics, Valuation Methodology, Date of Notification, Betterment, Disturbance or Incidental Cost, Injurious Affection, Severance, and Accommodation Works—are all perceived as significant, with Market Value, Injurious Affection and Severance recording the highest mean scores, while Disturbance or Incidental Costs and Accommodation Works exhibit strong consensus based on low standard deviations. These results suggest that discrepancies stem from a combination of technical, legal, and ethical considerations, indicating the need for clearer valuation guidelines on high-importance and recommending that future research expand the geographical scope, incorporate real case files, and include a broader sample of valuers to enhance transparency, consistency, and equity in compensation assessment.